Identification Of Candida Albicans In Saliva Patients With Type 2 Diabetes Mellitus At The Simalingkar Health Center Medan City - Fani Nuryana Manihuruk; Gultom , Atri Gustiana (Jurnal EduHealth, 2024)
Diabetes mellitus is a predisposing factor for the emergence of oral candidiasis. Increased blood glucose levels can also increase glucose levels in saliva. Excessive blood sugar levels in saliva stimulate the growth of Candida albicans on the mucosal surface, as a result, Candida albicans will be found in the saliva of DM patients. Oral candidiasis can attack mucosal tissues such as the mouth and pharynx and can be a complication of cancer. Purpose of this study was to identify candida albicans in the saliva of patients with type 2 diabetes mellitus at the Simalingkar Health Center, Medan City. Method This study is a descriptive study with a cross-sectional approach. The sampling technique was random. The number of samples identified in this study was 25 respondents, macroscopic and microscopic examinations were carried out, then the data were analyzed descriptively. The result of the descriptive analysis of the examination obtained the results of the study 56% positive Candida albicans, and 44% of respondents were negative for Candida albicans fungus. Conclusion The percentage value shows that most saliva samples from type 2 diabetes mellitus patients contain Candida albicans. These results emphasize the importance of routine monitoring of blood glucose levels to prevent the occurrence of oral candidiasis more effectively in type 2 diabetes melitus.